The sustainability of towards zero strategy: examining speeding, enforcement measures and road users' attitudes - Ebrahim, Zuhair (Curtin University, 2014)
The positive contributions of the electronic signs around school and non-school zones are real and need to be expanded. The shift of this vital contribution is coming from minimising harm with lesser fatalities. This is what 'Towards Zero Strategy' of Perth is pursuing. To continue this real achievement, speed enforcement will remain a crucial element, particularly when it is on the spot. Young drivers may start to response. If they don't, the speed awareness courses should influence them along with other speeders in a new sustainable jurisdiction.